ANALYSIS OF FARM EFFICIENCY OF PERTIWI VARIETY MELON IN GIRIWOYO DISTRICT - Erlyna Wida Riptanti (Universitas Muslim Indonesia, 2026)
The production of Pertiwi melon in Giriwoyo District, Wonogiri Regency, Central Java Province has experienced fluctuations in recent growing seasons. This phenomenon indicates potential inefficiency in farm management. This study aims to analyze the costs, revenues, and income of Pertiwi melon farming, as well as to evaluate the levels of technical, allocative, and economic efficiency based on the use of production inputs.The research employed a descriptive quantitative approach with a census method involving 37 farmers from three villages: Giriwoyo, Sendangagung, and Bulurejo. Data were collected through structured questionnaires and analyzed using the Cobb-Douglas production function combined with economic efficiency calculations.The results showed that Pertiwi melon farming is financially feasible, with an average net income of IDR 54,951,733 per growing season. Production inputs that were found to significantly influence yields include manure, NPK Mutiara fertilizer, SP-36 fertilizer, and pesticides. The average technical, allocative, and economic efficiency values were 0.81, 0.77, and 0.62, respectively.Overall, the findings suggest that farmers still need to optimize the use of production inputs to achieve higher efficiency levels. Enhancing managerial capacity and providing technical support are essential to ensure efficient and sustainable cultivation of Pertiwi melon